1994
DOI: 10.1136/bjsm.28.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Athletic footwear affects balance in men.

Abstract: Stable equilibrium during locomotion is required for both superior performance of sports and prevention of injuries from falls. A recent report indicated that currently available athletic footwear impairs stability in older men. Since this discovery, if confirmed, seems important to both competitive athletes and the physically active general public, we performed an experiment using similar methods on a younger population. We tested the hypothesis that midsole thickness is negatively, and hardness positively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 14 publications
3
48
0
1
Order By: Relevance
“…They include midsole material hardness, height of heel collar and outer sole slip resistance (frictional properties). The largest collection of work has been done on midsole material and control of balance by Robbins et al [3][4][5][6]. His investigations have involved both walking on a narrow beam and detecting ankle angle position in footwear that varied in hardness levels from soft (Shore A Scale 15) to hard (Shore A Scale 50).…”
Section: Introductionmentioning
confidence: 97%
“…They include midsole material hardness, height of heel collar and outer sole slip resistance (frictional properties). The largest collection of work has been done on midsole material and control of balance by Robbins et al [3][4][5][6]. His investigations have involved both walking on a narrow beam and detecting ankle angle position in footwear that varied in hardness levels from soft (Shore A Scale 15) to hard (Shore A Scale 50).…”
Section: Introductionmentioning
confidence: 97%
“…However, a direct comparison between both studies is not possible because of different mid-sole densities and methods to evaluate balance. It is possible that the extra thickness (compared to the other shoes tested) and softness of the mid-sole of the SU resulted in sensory insulation [13] by reducing afferent input to the brain regarding foot position. The FF was the thinnest of the shoe constructions and this may help explain in part why there were no significant differences in stability when wearing this shoe even though it specifically has a low-density foam mid-foot portion.…”
Section: Discussionmentioning
confidence: 92%
“…By combining these two (thickness and softness vs. thinness and hardness) balance failure increased by 217%. [13] Contrary to Robbins et al [13], Lord et al [14] reported no association between firmness (hard-soled; Shore A58 or softsoled; Shore A42) of shoe sole and balance ability. However, a direct comparison between both studies is not possible because of different mid-sole densities and methods to evaluate balance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Footwear stability is most frequently researched within the areas of athletic and high-heeled shoes, with papers mainly focusing on medial and lateral foot stability and postural sway [18][19][20]. The way the sole is constructed and the sole material properties have been shown to influence stability and comfort in elderly populations with a thick-soled shoe reducing stability and a thinner firmer sole material being more preferable [21].…”
Section: Introductionmentioning
confidence: 99%